2013
DOI: 10.1002/anie.201307822
|View full text |Cite
|
Sign up to set email alerts
|

Resonances in the Entrance Channel of the Elementary Chemical Reaction of Fluorine and Methane

Abstract: Extending the fully quantum-state-resolved description of elementary chemical reactions beyond three or four atom systems is a crucial issue in fundamental chemical research. Reactions of methane with F, Cl, H or O are key examples that have been studied prominently. In particular, reactive resonances and nonintuitive mode-selective chemistry have been reported in experimental studies for the F+CH4 →HF+CH3 reaction. By investigating this reaction using transition-state spectroscopy, this joint theoretical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
75
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 42 publications
2
75
0
1
Order By: Relevance
“…And lots of important works have been done by using it. [6][7][8][9][10] However, explanations to PADs are only qualitative in most cases, and rather limited works have been reported on how to calculate PAD of anions. [11][12][13][14][15][16][17] The PAD is the differential cross sections of photoionization or photodetachment.…”
Section: Introductionmentioning
confidence: 99%
“…And lots of important works have been done by using it. [6][7][8][9][10] However, explanations to PADs are only qualitative in most cases, and rather limited works have been reported on how to calculate PAD of anions. [11][12][13][14][15][16][17] The PAD is the differential cross sections of photoionization or photodetachment.…”
Section: Introductionmentioning
confidence: 99%
“…22 Nevertheless, the QCT study found that the CH vibrational excitation enhances the overall reactivity. More recently, an improved PES 4,35,38 has been developed by Palma, Westermann, Eisfeld, and Manthe by considering the spin-orbit coupling in the reactant channel (PWEM-SO), which provides a more accurate description of the reactant channel than the CSBB PES. In the transition-state and product region, the PWEM-SO PES is smoothly switched to the CSBB PES.…”
mentioning
confidence: 99%
“…Consequently, very long propagation times are required in the dynamical simulations. While detailed quantum mechanical calculations studying FCH 4 transition state spectra and low-lying pre-reaction complexes have been reported, 4,31,32,35,40 QD studies of reactive scattering have so far been restricted to low dimensionality studies of the F + CH 4 → HF + CH 3 reaction. 17,24,34 These calculations included a maximum of five coordinates and thus had to ignore important degrees of freedom.…”
mentioning
confidence: 99%
“…Im Zentrum seiner Forschung stehen die Reaktionsdynamik und die Spektroskopie. Er hat in der Angewandten Chemie über die Untersuchung der Dynamik der Reaktion zwischen Fluor und Methan berichtet 7 …”
Section: Gewählt …︁unclassified